COVID-19 and Mycobacterium coinfection in Brunei Darussalam: case series - Mani, Babu Ivan; Kishore, Panduru Venkata; Khine, Wai Yan; Thottacherry, Dilip Joseph; Chong, Pui Lin; Abdullah, Muhamad Syafiq; Asli, Rosmonaliza; Momin, Natalie Raimiza; Rahman, Noor Affizan; Chong, Chee Fui; Chong, Vui Heng (Western Pacific Surveillance and Response, 2023)
Coronavirus disease (COVID-19) and tuberculosis (TB) coinfection is expected to become more common in countries where TB is endemic, and coinfection has been reported to be associated with less favourable outcomes. Knowing about the manifestations and outcomes of coinfection is important as COVID-19 becomes endemic. During the second wave of the COVID-19 pandemic in Brunei Darussalam, we encountered seven patients with COVID-19 and Mycobacterium coinfection. Cases of coinfection included three patients with newly diagnosed pulmonary Mycobacterium infection (two cases of pulmonary TB [PTB] and one case of Mycobacterium fortuitum infection) and four patients who were already being treated for TB (three cases of PTB and one case of TB lymphadenitis). Among the new cases, one had previously tested negative for PTB during a pre-employment medical fitness evaluation and had defaulted from follow up and evaluation. One case died: a 42-year-old man with diabetes mellitus, chronic kidney disease and hypertension who had severe COVID-19 and needed urgent dialysis and supplemental oxygen. All other patients recovered from COVID-19 and completed their TB treatment.